ANALYSIS OF STRUCTURE AND ANTIMICROBIAL ACTIVITY OF CeO2 AND Nd2O3 NANOPARTICLES - Hanif Yuliani; Rina Dewi Mayasari; Eryanti Kalembang; Yelvia Deni; Defi Rahma Santi; Putri Widya Pangestika; Setyo Purwanto; Bambang Sugeng; Suyanti Suyanti; Moch. Setyadji (Program Studi Fisika Universitas Negeri Jakarta, 2019)
Cerium oxide (CeO2) and Neodymium oxide (Nd2O3) nanoparticles using local content have been synthesized by precipitation method. The CeO2 and Nd2O3 nanoparticles were characterized by X-Ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) to analyze the material phase and structure. The XRD spectrum shows that CeO2 and Nd2O3 nanoparticles have face-centered cubic and hexagonal, and cubic, respectively. The anti-microbial activity of CeO2 and Nd2O3 nanoparticles was analyzed by diffusion method using gram-negative bacteria (E. coli, S. aureus, P. aeruginosa), and gram-positive bacteria (S. entericatyphi, L. monocyogenes), and fungus (C. albicans). The result confirms that CeO2 and Nd2O3 nanoparticles have the capability of microbial pathogen inhibition. The CeO2 nanoparticles have the effective activities of inhibition for the microbial of S. aureus and S. entericatyphi, whereas Nd2O3 nanoparticles can inhibit the microbial of P. aeruginosa, S. entericatyphi, and L. monocyogenes.